2012
DOI: 10.1128/iai.00215-12
|View full text |Cite
|
Sign up to set email alerts
|

A Chimeric Toxin Vaccine Protects against Primary and Recurrent Clostridium difficile Infection

Abstract: fThe global emergence of Clostridium difficile infection (CDI) has contributed to the recent surge in severe antibiotic-associated diarrhea and colonic inflammation. C. difficile produces two homologous glucosylating exotoxins, TcdA and TcdB, both of which are pathogenic and require neutralization to prevent disease occurrence. However, because of their large size and complex multifunctional domain structures, it has been a challenge to produce native recombinant toxins that may serve as vaccine candidates. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 65 publications
8
87
1
Order By: Relevance
“…38 The N terminus encompassing the GTD and CPD domains is more conserved between historical and epidemic strains. In our previous study 37 and consistent with others, 35,36 we indicated that the N-terminus of TcdB was able to elicit a protective antibody response. In contrast, the RBD of TcdA has potent adjuvant activity 40 , and has been used as vaccine candidates in several studies.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…38 The N terminus encompassing the GTD and CPD domains is more conserved between historical and epidemic strains. In our previous study 37 and consistent with others, 35,36 we indicated that the N-terminus of TcdB was able to elicit a protective antibody response. In contrast, the RBD of TcdA has potent adjuvant activity 40 , and has been used as vaccine candidates in several studies.…”
Section: Discussionsupporting
confidence: 65%
“…We also found that the neutralizing epitopes in TcdB are located in the N terminus 37 in addition to other domains. 32 Moreover, the N terminus of TcdB is more conserved than its RBD.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…A Phase Ⅱ trial of this vaccine, currently underway in the US, is being conducted to assess primary CDI prevention in 650 at risk adults [225] . Also in development is a chimeric antitoxin vaccine using an endotoxin free expression system from Bacillus metaerium, which was capable of producing neutralizing antitoxins and preventing spore-induced relapse in CDI [226] .…”
Section: Vaccinementioning
confidence: 99%